Visibility fringe reduction due to noise-induced effects: Microscopic approach to interference experiments - Villar, Paula Ines (2007)
Decoherence is the main process behind the quantum to classical transition. It is a purely quantum mechanical effect by which the system loses its ability to exhibit coherent behavior. The recent experimental observation of diffraction and interference patterns for large molecules raises some interesting questions. In this context, we identify possible agents of decoherence to take into account when modeling these experiments, and study their visible (or not) effects on the interference pattern. We thereby present an analysis of matter wave interferometry in the presence of a dynamic quantum environment, and study how much the visibility fringe is reduced and in which timescale the decoherence effects destroy the interference of massive objects. Finally, we apply our results to the experimental data reported on fullerenes and cold neutrons. © World Scientific Publishing Company.